Effects of the Brain Wave Modulation Technique Administered Online on Stress, Anxiety, Global Distress, and Affect During the First Wave of the COVID-19 Pandemic: A Randomized Clinical Trial - Cozzolino, Mauro; Celia, Giovanna; Girelli, Laura; Limone, Pierpaolo (Frontiers in Psychology, 2021)
This study aims to evaluate the effects of an innovative mind-body practice named the brain wave modulation technique (BWM-T) on stress, anxiety, global distress, and affect. The technique was administered online through a web-based video conferencing platform. The intervention started on week four of the first quarantine in Italy (week commencing 30th March 2020), for a duration of four weeks and ended before lockdown measures were loosened. 310 people participated in the study, mean age 28.73 years old (SD = 9.16), 77,8% women. Of these, about half were randomly assigned to the experimental group and the other half served as controls. Participants completed online psychological tests before and after the intervention. 266 people (144 experimental, 122 controls) completed the post-intervention tests. Consistent with our hypothesis, the study’s findings indicate a reduction in the levels of stress, anxiety, global distress, and negative affect in the experimental group, compared to the control group. Moreover, the experimental group also showed higher levels of positive affect, compared to controls after the intervention. The present findings add to the current literature in suggesting that the BWM-T reduced stress not only when administered face-to face but also when administered online during the COVID-19 pandemic. Moreover, we also noted that the BWM-T has an effect on anxiety, global distress, and affect, which we had not investigated in previous studies.